Block Copolymer‐Templated Approach to Nanopatterned Metal–Organic Framework Films. Issue 16 (4th July 2017) - Zhou, Meimei; Wu, Yi‐nan; Wu, Baozhen; Yin, Xianpeng; Gao, Ning; Li, Fengting; Li, Guangtao
Abstract: The fabrication of patterned metal–organic framework (MOF) films with precisely controlled nanoscale resolution has been a fundamental challenge in nanoscience and nanotechnology. In this study, nanopatterned MOF films were fabricated using a layer‐by‐layer (LBL) growth method on functional templates (such as a bicontinuous nanoporous membrane or a structure with highly long‐range‐ordered nanoscopic channels parallel to the underlying substrate) generated by the microphase separation of polystyrene‐ b ‐poly(2‐vinylpyridine) (PS‐ b ‐P2VP) block copolymers. HKUST‐1 can be directly deposited on the templates without any chemical modification because the pyridine groups in P2VP interact with metal ions via metal‐BCP complexes. As a result, nanopatterned HKUST‐1 films with feature sizes below 50 nm and controllable thicknesses can be fabricated by controlling the number of LBL growth cycles. The proposed fabrication method further extends the applications of MOFs in various fields. Abstract : Filmmaking : Nanopatterned HKUST‐1 films could be obtained via layer‐by‐layer growth on periodic nanostructures formed by microphase separation of polystyrene‐ b ‐poly(2‐vinylpyridine (PS‐ b ‐P2VP).